Theoretic Study of Image Fusion Techniques – A Survey - Maurya, Anamika; Tiwari, Rajinder (International Journal of Computer Sciences and Engineering, 2014)
Image fusion is the hottest research subtopic of image processing. Fusion is basically extraction of best inputs and conveying to the output. For making an image, which is more suitable for segmentation, extraction of features, object recognition and human visual system, Image fusion is frequently used. It combines complimentary information from different image of the same scene in a single image. Image fusion can be performed at four different process levels which are signal, pixel, feature and decision level according to the stage at which levels fusion takes place. This paper provides survey of some of the various existing techniques applied for image fusion and comparative study of all techniques concludes better approach for its future research. In this paper we also try to find it out what are things that were neglected by the researchers, so our main objective was to find out the gaps in existing literature.